GENRE-BASED APPROACH TO TEACHING SPEAKING : a case study at a state junior high school in Bandung - Abdullah, Cep Ubad (2015)
ABSTRAK Penelitian ini bertujuan untuk menganalisa implementasi GBA dalam pengajaran speaking serta bagaimana kemampuan berbicara bahasa Inggris siswa meningkat melalui pengajaran GBA. Desain penelitian yang digunakan adalah studi kasus kualitatif yang menggunakan 3 jenis instrumen untuk mengumpulkan data berupa observasi, wawancara, dan tes. Adapun yang merupakan responden dari penelitian ini adalah seorang guru bahasa Inggris serta satu kelas 8 di salah satu SMP Negeri di kota Bandung. Setelah data yang didapat dianalisis, didapati bahwa GBA dapat diimplementasikan dalam pengajaran speaking dengan melaksanakan seluruh proses pembelajaran secara berurutan yang meliputi BKOF, MOT, JCOT, serta ICOT serta dengan cara mengintegrasikan kegiatan berbicara di setiap proses pembelajaran. Pelaksanakan proses pembelajaran secara berurutan sangat membantu siswa secara perlahan untuk memahami bagaimana membuat teks recount. Selain itu, dengan guru selalu menekankan agar siswa berbicara menggunakan bahasa Inggris, siswa pun menjadi termotivasi untuk selalu menggunakan bahasa Inggris. Temuan kedua dari penelitian ini adalah bahwa kemampuan berbicara siswa meningkat dengan adanya konsep ZPD, bilingualism, dan explicit teaching. Ketiga faktor tersebut dikonfirmasi baik oleh guru maupun murid sebagai faktor-faktor yang efektif meningkatkan kemampuan berbicara siswa. ---------- This study investigated the implementation of Genre-Based Approach in teaching speaking and how students' speaking ability, particularly an ability to talk about their holiday using recount text, was developed through GBA. The design used was a case study utilizing three instruments namely observation, interview, and test. Involved in this paper serving as respondents were a teacher and a class of eighth graders at a state junior high school in Bandung, Indonesia. Having analyzed the data gained through the aforementioned three instruments, this study found out that GBA was applicable in teaching speaking by implementing teaching cycles of GBA covering Building Knowledge of the Field (BKOF), Modeling of the Text (MOT), Joint Construction of the Field (JCOT), and Independent Construction of the Field (ICOT) as well as infusing speaking activities in each cycle. Each cycle was implemented orderly so that students went step by step in producing their spoken text of recount. To help the students practice their speaking, the teacher encouraged them to speak in English as often as possible so that she infused speaking activities in each of the cycles. This paper also revealed that students' speaking ability was improved since GBA promoted ZPD, bilingualism, and explicit teaching that seemed to be useful and effective in students' speaking ability development. Those three factors were confirmed by either the teacher or the students to be helpful in developing the students' speaking ability.